Increased adherence to influenza vaccination among Palermo family pediatricians: a study on safety and compliance of qLAIV vaccination - Claudio Costantino; Fabio Tramuto; Nicole Bonaccorso; Maria Carmela Lo Giudice; Francesco Balsamo; Alessandro Carubia; Luciano D'Azzo; Santo Fruscione; Martina Sciortino; Tania Vitello; Luigi Zagra; Alessia Pieri; et al. (BMC, 2024)
Abstract Background Influenza represents a serious public health threat, especially for the management of severe cases and complications of the disease, requiring the implementation of control measures. We aimed to assess the acceptance and impact of qLAIV vaccination among a representative sample of family paediatricians (FPs) operating in Palermo Local Health Authority (LHA). To this end we evaluated vaccination coverage rates, comparing it with that observed in Sicilian context, while actively monitoring possible adverse reactions and their severity. Methods An observational descriptive non-controlled study was conducted in two phases, from September 2022 to June 2023. The first phase involved a formative and educational intervention with a pre-intervention questionnaire to assess the knowledge and attitudes of FPs on paediatric influenza vaccination. The second phase consisted of an active surveillance on qLAIV safety and acceptance among the paediatric population assisted by the participating FPs, from October 2022 to April 2023. Frequencies, chi-squared tests, and comparisons statistics were performed using Stata/MP 14.1. Results The overall coverage rate among the paediatric population involved in the intervention was 13.2%, with an I.M./qLAIV ratio of vaccine administered of 1/4.25. This coverage rate was significantly higher (p-value <0.001) when compared to the average values reported in the population under the Palermo Local Health Authority (LHA) (6.7%) and in the entire Sicily (5.9%). Adverse events in the qLAIV group were mild, with only 3.3% experiencing them, primarily presenting as a feverish rise (3.2%). No severe adverse reaction was reported. Conclusions The educational intervention significantly raised paediatric influenza vaccination rates among the participating FPs, and in general improved influenza vaccination coverage rates in the Palermo's LHU. Minimal, non-serious adverse events underscored the vaccine's safety. Training sessions ensured paediatricians stayed informed, enabling them to provide comprehensive information to parents for secure and informed vaccination decisions in their practices.